Essays on economics of marriage - Marçal, Lorena Hakak (2016)
Society has changed in the past decades raising questions to be asked by social scientists and their impacts on family units. In this thesis we aim to analyze how agents’ decisions on marriage and education can be interconnected assuming that men and women have preferences for intra-group marriage. In our framework we find that preferences for intra-group marriage can increase the proportion of men and women who decide to get married and study. We also show that empirically for Brazilian data there is a positive assortative mating between people with same traits, such as, education, religion or race. In addition, married couples that share the same religion tend to have the same level of schooling. We investigate how changes in marital sorting, educational composition and returns to education that occurred in Brazil in the last years can impact in household income inequality. We calculate counterfactual scenarios for Gini Coefficient keeping one of these three variables fixed in one year and comparing the counterfactual values with the actual one. If marriage were formed randomly, the Gini Coefficient would be lower than the actual one. Keeping the returns to education fixed in year 2014 we also show that the counterfactual Gini would be lower than the actual one.